Design and analysis of nanostructured optical fiber and surface plasmon devices - Wang, Guanghui (2012)
The normal single mode optical fiber (SMF) with diameters much bigger than optical wavelength has presented lots of successful applications in optical communications. However, minimizing the width of the waveguides is desirable for many integrated optics device applications, and this becomes the main development tendency of modern photonics technologies. The microstructured/nanostructured fiber or micro-nanofiber (MNF), acting as a mode squeezer, provides a nature bridge from macrostructure world to microstructure/nanostructure world. The diameter of air-cladding MNFs is always comparable to or less than the wavelength of propagating light. With large index difference, it still can guide the mode with strong confinement and small bending loss. Furthermore, its guiding properties are totally different with that of normal SMF, which could provide a large number of new applications. MNFs become the potential building blocks for miniature photonic devices. Comparing with micro- and nano-photonics based on lithographic technology, MNFs have several advantages: (1), significantly lower losses for a given index contrast, (0.001dB/mm); (2), the ability of micro-assemblage in 3D; (3), significantly low cost for the experiments;(4), controllable evanescent field and confinement properties.